Effects of post-deposition annealing temperatures on the composition of interfacial layer at germanium (Ge) /aluminium oxide (Al2O3) - Siti Kudnie Sahari,; Nik Amni Fathi Nik Zaini Fathi,; Azrul Azlan Hamzah,; Norsuzailina Mohamed Sutan,; Zaidi Embong,; Suhana Mohamed Sultan,; Muhammad Kashif,; Marini Sawawi,; Hasanah, Lilik; Rohana Sapawi,; Kuryati Kipli,; Abdul Rahman Kram,; et al. (Penerbit Universiti Kebangsaan Malaysia, 2019)
The understanding of chemical bonding structure of high k dielectrics/Germanium (Ge) interface is upmost importance in order to form a good quality dielectric/Ge interface in fabricating Ge metal oxide semiconductor field effect transistor (MOSFETs). In addition, there is still no detail explanation on the interfacial growth of dielectrics/Ge under the influenced of different temperature of post deposition anneal. In current work, the effects of post deposition anneal (PDA) temperature between 400°C and 600°C on the chemical composition of interfacial layer between Ge and Al2O3 were examined by X-ray photoelectron spectroscopy (XPS). Investigation on thermal stability and structural characteristics for gate structure of Al2O3 dielectric grown on Ge by RF sputtering was done by analyzing X-ray photoelectron spectroscopy (XPS) spectra. It is observed that the oxygen deficient region in interfacial layer (IL) is enhanced rather than fully oxidized Al2O3 with increased PDA temperatures. These undesired phenomena caused shrinkage of IL at Ge/Al2O3 interface at higher temperature of 600°C.